GE_GERICHTE A/4153/2005 vom 13. Oktober 2005 - GE Cour de justice (2005)
; PRÉVOYANCE PROFESSIONNELLE ; PRÉVOYANCE PROFESSIONNELLE SELON LA LPP ; LIBRE PASSAGE(ASSURANCES) ; DIVORCE ; PARTAGE(SENS GÉNÉRAL) ; TAUX D'INTÉRÊT | LFLP; LFLP 25a; LFLP 22; LFLP 24; OLP 8a; OPP 2 12